DEATH AND REINCARNATION AS INSPIRATION OF CREATION FINE ARTWORK - Kariana, I Nengah; Wirakesuma, I Nengah; Ruta, I Made (Program Studi Seni Murni ISI Bali, 2025)
This report contains a description of the creation of works of art that take the theme